Guide For Teaching Phonetics Through Music (2018)
During the pedagogical practice of the degree program in Spanish and English Teaching, implemented at the Mercedes Nariño Women's High School, it could be perceived that two of the most complex skills to develop in teenagers are the speaking and listening skills in the English language. Considering the previous statement, English teachers confront a big challenge when teaching both abilities in the classroom, due to the fact that teachers are not clear about what to teach, when and how to implement the skills mentioned above in their activities. As a result of this problem, the teacher does not pay attention to the development of the students´ listening and speaking skills and focuses on improving other skills, while they do not feel comfortable teaching comprehension and pronunciation in English. As of this necessity, it is proposed to elaborate a didactic unit that proposes a guide for the teacher that allows to implement basic phonics concepts in activities related to music so that students improve their speaking and listening skills.